Tertúlias literárias dialógicas e leitura dialógica com pessoas idosas - Batisteti, Éverton Madaleno (2022)
Currently, the elderly population in Brazil exceeds 30 million people and it is predicted that by 2050 the number of elderly people will approach 70 million. Considering this demographic trend and the rights of the elderly population guaranteed by legal provisions, such as the Statute of the Elderly, it becomes evident the need to discuss how educational activities aimed at Lifelong Learning can contribute to the process of Healthy Aging, ensuring a life capable of promoting all the functional abilities that allow the elderly to be and do what they value. Therefore, considering a specific Successful Educational Action, which has as its theoretical reference the seven principles of the Dialogical Learning Theory (namely: Equalitarian Dialogue, Cultural Intelligence, Instrumental Dimension, Transformation, Meaning Making, Solidarity and Equality of Differences), it was aimed in this qualitative research, of descriptive type, to highlight transformative aspects and exclusionary aspects, from the perspective of participating seniors, of dialogical literary tertulia spaces as favorable to healthy aging. It is understood that the dialogical reading of classical works allows these participants a continuous process of Lifelong Education, besides promoting spaces for social interaction and incentive to other activities. From the analysis of ten communicative reports with elderly people (average age of 71.6 years) and participants of the same group of Dialogical Gathering, it was possible to establish the transforming elements (that favor institutions and subjects to reach the necessary instruments for the exercise of equality) or, in contraposition, the excluding elements. Using the Communicative Methodology, which seeks to empower all the voices of the people involved in the research, breaking with the interpretative hierarchy, we expanded the understanding of the Dialogical Literary Gatherings not only as an educational activity capable of expanding the instrumental dimension of the contents of its participants, but also as i) a space for personal strengthening and overcoming of traumas and attitudinal barriers; ii) promoter of other activities aimed at healthy aging; iii) capable of expanding relationships and guiding relationships for interactions based on communicative acts. It is hoped that this work will contribute to the field of education, gerontology, and all those involved with the well-being and guarantee of the rights of the elderly, emphasizing the importance of long-lasting activities for the strengthening of bonds and their benefits.